Acetals from primary alcohols with the use of tridentate proton responsive phosphinepyridonate iridium catalysts. Issue 102 (24th October 2016) - Sahoo, A. R.; Jiang, F.; Bruneau, C.; Sharma, G. V. M.; Suresh, S.; Achard, M.
Abstract : The association of the new phosphinepyridonate ligands along with an iridium metallic precursor resulted in the selective acetalization of various primary alcohols via a formal dehydrogenative coupling reaction. Abstract : The association of the new phosphinepyridonate ligands along with an iridium metallic precursor resulted in the selective acetalization of various primary alcohols via a formal dehydrogenative coupling reaction.